HIV‐1 genotype is independently associated with immunodeficiency progression among Chinese men who have sex with men: an observational cohort study. Issue 5 (21st December 2019) - Liang, Y; Han, Z; Shui, J; Cheng, W; Zhong, F; Cai, Q; Wang, H; Wu, H; Xu, H; Tang, S
Abstract : Objectives: HIV‐1 genetic diversity is increasing among men who have sex with men (MSM) in China, but the association of HIV‐1 genotype with disease progression remains to be elucidated. Methods: We collected data in an observational longitudinal cohort study of 860 HIV‐1‐infected MSM in Guangzhou, China between January 2008 and March 2017. Kaplan‐Meier analysis and Cox proportional hazard model were used to predict the time from HIV‐1 diagnosis to immunodeficiency progression (CD4 cell count < 200 cells/μl) as well as adjusted hazard ratio (aHR). Results: CRF01_AE and HIV‐1 subtype B infection were associated with higher percentage of patients progressed to immunodeficiency and higher incidence of immunodeficiency than infection with CRF07_BC or CRF55_01B. Compared with CRF07_BC, the time from HIV‐1 diagnosis to immunodeficiency were different among the major HIV‐1 genotypes, which ranked as follows, in descending order: CRF07_BC (7.03 years) > CRF55_01B (5.71 years, P = 0.014; aHR 3.752, P = 0.0923) > CRF01_AE (5.18 years, P < 0.001; aHR 4.733, P = 0.0152). HIV‐1 genotype, viral load and baseline CD4 T‐cell count were three independent variables associated with disease progression. Conclusions: Our results confirm differential rates of immunodeficiency progression as a function of HIV‐1 genotype. The impact of HIV‐1 genotype on HIV epidemics, patient management and prevention should be further investigated.